The influence of military training on emotional intelligence in the troops of a military institution 2003 - Robles Mori, Herbert (2003)
A total 229 pertaining to the army police armored pertaining to the army, commando troop, campaign troop and special troop soldiers belonging to the different contingents of military training, were submitted to a descriptive comparative study where the objective was to describe and compare the influence of the military training programs over the emotional intelligence of the troop staff. It was found an influence of the military training that in relation to some units the where positive influences and in the other units they were negative influences.